Effect of Mixed Salts on Atmospheric Corrosion of 304 Stainless Steel. Issue 11 (1st January 2019) - Guo, Liya; Mi, Na; Mohammed-Ali, Haval; Ghahari, Majid; Plessis, Andrew Du; Cook, Angus; Street, Steven; Reinhard, Christina; Atwood, Robert C.; Rayment, Trevor; Davenport, Alison J.
Abstract : Atmospheric corrosion of stainless steel can take place when airborne salt particles deposit on the metal surface, forming droplets when the relative humidity (RH) reaches a critical value: the deliquescence relative humidity of the salt. Most work to date has focused on single salts such as MgCl2 or NaCl. In the present work, the effect of mixed salts is investigated at 45% RH, above the deliquescence relative humidity of MgCl2 but below that of NaCl. Dish-shaped pits were found in pure MgCl2 solutions and mixed solutions. Crevice corrosion takes place under NaCl crystals. This is shown both with ex situ measurements and in situ time-dependent measurements using X-ray microtomography, where pit growth was also monitored.